Education and training in public administration and development: what does the customer really want and are we prepared to provide it? - Rubienska, Annie (2001)
This article examines some of the difficulties arising from the introduction of market forces into the field of higher education. In particular it notes how the changing demands of sponsors and other key players, coupled with recent trends in teaching and learning methods, have caused providers of education and training in development to review `core products' and modify the style of service delivery to accommodate the changing expectations of `customers.' - Reproduced
Keywords: Training; Education; Public administration